If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 4(7 + 3w) = 0 2w + (7 * 4 + 3w * 4) = 0 2w + (28 + 12w) = 0 Reorder the terms: 28 + 2w + 12w = 0 Combine like terms: 2w + 12w = 14w 28 + 14w = 0 Solving 28 + 14w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 14w = 0 + -28 Combine like terms: 28 + -28 = 0 0 + 14w = 0 + -28 14w = 0 + -28 Combine like terms: 0 + -28 = -28 14w = -28 Divide each side by '14'. w = -2 Simplifying w = -2
| 20X+10=20X-10 | | 3(x-6)=54 | | .16(24)+.04=.08(6+x) | | -17x+32=11x^2-17 | | 2y+4x+5=180 | | 9th-4+3(a-11)=23 | | 70=28+7x | | 20x+2y=-16 | | 2x+3=26 | | 2p-5r=q | | 20x-4=12x-20 | | 5*14-(2*1+4-1)= | | 8y-10y-y=-y | | 2(x+3)=5x+11 | | -13.4-0.5=10.1 | | .2x+5=22 | | 6.1+11.1=8s+7.1-7s | | 21-7K=-3K+4 | | X/5-2=0 | | 5*0-(2*0+4-0)= | | 16.7d=-3d+2 | | 4x-3y=5findy | | 4y=3y+33 | | 20-5s+4=-s-20 | | (90-x)=5x | | m^2+mn-56n^2=0 | | 5x=(90-x) | | -3n=29 | | -6g+20=-10g | | 43=-9-14x | | 12x+5=149 | | 10y-8y-y=0 |